Defect-modulation in α-Ga2O3 molecular beam epitaxial photodetector investigated through pulsed-light persistent-photoconductivity - Hongliang Chang; Yanqing Jia; Abdullah Alquwayzani; Xu Zhang; Redha H. Al Ibrahim; Mohamed Ben Hassine; Dalaver H. Anjum; Qingxiao Wang; Mohamed Nejib Hedhili; Jiarui Gong; Qiaoqiang Gan; Zhenqiang Ma; et al. (APL Materials)
α-phase gallium oxide (Ga2O3) features a corundum crystal structure that closely matches the low-cost sapphire substrate commonly used in epitaxy, enabling researchers to perform precise and controllable Ga2O3 epitaxy. It thus offers an excellent material platform for the development of high-power devices and deep ultraviolet photodetectors (DUV-PDs). In this study, we altered the epitaxy properties of α-Ga2O3 grown on m-plane sapphire substrates by changing the growth parameters of oxide molecular beam epitaxy and demonstrated effective modulation of the oxygen vacancy (VO) dependent persistent photoconductivity (PPC) behavior. This gave rise to a tunable paired-pulse facilitation (PPF) index in the fabricated α-Ga2O3-based DUV-PDs. Using α-Ga2O3 grown on bare m-plane sapphire at 500 °C as a benchmark (α-Ga2O3-500 °C), we effectively altered the VO contribution by either increasing the growth temperature to 570 °C or introducing a step-graded α-(AlxGa1−x)2O3 buffer. Photoluminescence and x-ray photoelectron spectroscopy analyses verified the variations in VO incorporation within α-Ga2O3 grown under different conditions. Finally, owing to the higher incorporation of VO defects within the material, the DUV-PD fabricated based on the α-Ga2O3–500 °C sample exhibited the most pronounced PPC behavior, achieving a maximum PPF index of 143% under a −1 V bias—representing a regulation amplitude of 26.5% compared to the control devices. The dominant VO defects in α-Ga2O3 and variable range hopping led to the PPC behavior observed in the fabricated devices. Our investigation highlights the feasibility of tunable PPC performance in α-Ga2O3-based devices for x-ray to DUV detection and solar-blind neuromorphic vision systems, potentially in harsh environments.